The Last Bastion of Rehabilitation: contextualizing Youth Correctionalism in Canada - Adorjan, Michael (The prison journal, 2018)
This article draws on research conducted with Canadian provincial correctional officers who have experience with youth in closed-custodial settings since the enactment of the 2003 Youth Criminal Justice Act. In Canada, where attempts to avoid a full embrace of the punitive turn seem to be persistent, we examine youth justice as the “last bastion” of the rehabilitative ideal as mediated by youth correctional officers. Our findings reveal that while officers retain a clear commitment to the ideal of rehabilitation and a desire to “save” young people, they are increasingly under siege by the changing context of prison, shifting managerial priorities, and the paradox of trying to help convicted youth in an inherently punitive environment.